Disciplines and practices for selection and workplace orientation within an American company - Kozák, Anita (Applied Studies in Agribusiness and Commerce, 2013)
The primary objective of this essay is to present how selection and orientation at the workplace are regulated and practiced at an American profit oriented company. Moreover, considering these practices to outline the disciplines which determine and influence them. The first part of this essay is a literature review which specifically illustrates various perspectives of selection and orientation at the workplace. Following this review, the objectives of this paper are enumerated. The next part presents the case study, the half-structured interview and the questionnaire methods used for this research. The results and the discussion parts are separated, because the results part shows how selection and orientation work in practice and then, by examining the results in some detail, the discussion part presents the disciplines which have been extrapolated. In order to support the conceived disciplines this paper also seeks to examine the most important supporting factors in the procedure of work orientation. General and professional/organizational factors of workplace orientation have been collected. Quantitative data from an empirical analysis is used for the research. Qualitative data is a part of a future dissertation. Questionnaires were completed by 80 employees at a distributor company in the United States of America. The results clearly show that the following disciplines should be maintained through these HR processes: equal opportunity, importance of professionalism, documentary, checking, support and continuance.